2022
DOI: 10.1111/jog.15401
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hypertensive disease and small for gestational age infants in twin pregnancy: A systematic review and meta‐analysis

Abstract: Aim: The review is to explore the connection between gestational hypertension diseases (GHD) and small for gestational age (SGA) in twin pregnancies. Methods: According to the recommendations of PRISMA, relevant studies were systematically searched through PubMed, Web of Science, Cochrane Library, Embase from inception until January 16, 2022. Subgroup analysis was performed according to chorionicity and diagnostic criteria of SGA. Odds ratios (OR) were assessed to judge the link between GHD and SGA in twin pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The comparatively asymmetrical growth pattern in twin pregnancies, where compared with singletons, growth lag is evident from around 30–32 weeks’ gestation, supports the concept that the intrauterine environment becomes constrained in its ability to sustain growth in twin foetuses [19]. When stratified by chorionicity, the association of hypertensive disorders of pregnancy and foetal growth restriction (FGR) is stronger in dichorionic than monochorionic twin pregnancies [20].…”
Section: Growth Trajectory Of Twins Versus Singletonsmentioning
confidence: 79%
“…The comparatively asymmetrical growth pattern in twin pregnancies, where compared with singletons, growth lag is evident from around 30–32 weeks’ gestation, supports the concept that the intrauterine environment becomes constrained in its ability to sustain growth in twin foetuses [19]. When stratified by chorionicity, the association of hypertensive disorders of pregnancy and foetal growth restriction (FGR) is stronger in dichorionic than monochorionic twin pregnancies [20].…”
Section: Growth Trajectory Of Twins Versus Singletonsmentioning
confidence: 79%
“…For neonatal outcomes, HDP was found to increase the risk of low birth weight, SGA, and NICU admission but did not influence Apgar <7 scores. Recently, Wang et al ( 33 ) have also shown that HDP increases the risk of SGA in twin gestations. However, their review was restricted to only SGA, and only seven studies were included.…”
Section: Discussionmentioning
confidence: 99%